The effect of progesterone on the anesthetic and analgesic requirements for ovariohysterectomy in the dog - KOSTAKIS, CH.; ANAGNOSTOU, T.; SAVVAS, I.; VERVERIDIS, CH.; KOURELIS, A. (Journal of the Hellenic Veterinary Medical Society, 2019)
The objective of the current study was to investigate the effect of serum progesterone concentration, either endogenous, during the ovarian cycle and pregnancy, or exogenous, when administered during anestrus, and of its active metabolite allopregnanolone, on anesthetic and analgesic requirements, as well as post-operative pain intensity, for the performance of ovariohysterectomy in dogs. One hundred and fifty healthy female dogs, which were admitted to our clinic for elective ovariohysterectomy, were included in the present study. They were allocated to 6 groups according to the stage of the ovarian cycle and the corresponding serum progesterone co ncentration. The six groups consisted of dogs in anestrus (group A), in anestrus which received intramuscular progesterone injections prior to surgery (group Ap), dogs in diestrus (group D), in diestrus which received subcutaneous aglepristone injections prior to surgery (group Da), in diestrus which received oral trilostane prior to surgery (group Dt) and dogs in pregnancy of duration of 28-42 days (group P). Serum progesterone concentrations were measured in all dogs before and after any hormonal treatment and serum allopregnanolone concentrations were measured in selected dogs from all groups. The required dose of propofol for induction of anesthesia and the required isoflurane concentration for maintenance of anesthesia and the need for intraoperative fentanyl administration and extra postoperative pethidine analgesia were recorded. After statistical analysis, there were no significant differences between groups, regarding their anesthetic or analgesic requirements, that could be attributed to serum progesterone and/or allopregnanolone concentration. However, moderate correlations within certain groups were noted. Serum progesterone or allopregnanolone concentrations do not seem to have an effect on anesthetic and analgesic requirements for ovariohysterectomy in the dog or any potential effect is weak enough to be masked by the action of anesthetic premedication and/or analgesic and/or anaesthetic drugs used.